Analisis Kesalahan Konseptual Siswa Dalam Menentukan Nilai Kosinus Sudut Tumpul Berdasarkan Taksonomi Ashlock - Ashari, Nur Wahidin; Salwah, Salwah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study analyzes students' conceptual errors in determining the value of trigonometric functions, specifically , using Ashlock's Taxonomy of Errors. Two cases of students' work were analyzed. In the first case, the student correctly performed the calculation for the magnitude of the horizontal projection but failed to apply the appropriate negative sign for cosine in the second quadrant, indicating a partial but incomplete understanding of trigonometric sign rules. In the second case, the student demonstrated a more fundamental error by choosing an entirely irrelevant solution strategy and using arbitrary values in their calculations. This suggests fragmentation of knowledge and difficulty in coherently integrating mathematical concepts to solve the problem. Overall, these findings highlight that students' errors in trigonometry often stem from misconceptions or underdeveloped conceptual understanding. Didactic implications suggest the need for instruction that emphasizes a relational understanding of basic trigonometric definitions, the relationship between angles-quadrants-signs, and the development of students' ability to select relevant problem-solving strategies.